UiTM health festival 2025: sihat sepanjang hayat, merdeka sepanjang zaman - Mohamad Asraff, Muhamad Syazni; Mohamad Salleh, Muhammad Muzzammil; Khebir, Muhammad Hariz ‘Ammar; Dashuki, Abdul Rahman; Ismail, Nurhuda; Isa, Mohamad Rodi; Jamil, Ahmad Taufik; Ibrahim, Khalid; Xin Wee, Chen (Faculty of Medicine, 2025)
The Merdeka 360: Kesihatan Menyeluruh Health Carnival was held on 23 August 2025, at Dewan Majlis Perbandaran Teluk Intan, Taman Desa Aman. The event was organised by the Public Health Department, Faculty of Medicine UiTM, in collaboration with the Hilir Perak District Health Office, Jabatan Perpaduan, and Kawasan Rukun Tetangga Taman Desa Aman, Teluk Intan, Perak. This programme, led by fourth-year undergraduate medical students, was supervised by Dr. Nurhuda Ismail, Associate Professor Dr. Mohd Rodi Isa, Dato’ Dr. Khalid Ibrahim, and Associate Professor Dr. Ahmad Taufik Jamil.